Pelatihan Pembuatan Makanan Bergizi Seimbang Bagi Kader Posyandu dan Bina keluarga Balita (BKB) Desa Sumerta Kaja Kota Denpasar - Arik Agustina; IGA Melistyari Dewi; Ayu Suwita Yanti (Jurnal Masyarakat Mengabdi Nusantara, 2024)
Balanced nutritional food is daily food that contains nutrients in the type and amount that suit the body's needs. The aim of this activity is to provide training and understanding regarding making balanced nutritious food for Posyandu and Toddler Family Development/BKB cadres in Sumerta Kaja Village. The methods used in this training are preliminary studies, preparation of training materials, preparation and procurement of financial resources, implementation of training, monitoring and evaluation and dissemination of results. This training involved Posyandu Cadres, Toddler Family Development, and mothers in Sumerta Kaja Village. Through this training, the Posyandu and Toddler Family Development Cadres in Sumerta Kaja Village were very enthusiastic and were able to provide more varied and nutritionally balanced food for the children.